Empowerment through access to energy loan products : a case study of FINCA - Uganda - Namyalo, Margaret (Kampala, 2013)
Unpublished dissertation (M.A. Gender Studies) - Makerere University , 2013.
Includes bibliographical references.
Keywords: Women in development -- Uganda; Women -- Uganda -- Economic development; Microfinance -- Uganda